Les contacts linguistiques entre les Celtes et les Ibères à travers l’onomastique (Vallée de l’Ebre, Sud de la France) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This article is a presentation of a PhD work in progress, dealing with Iberian and Celtic onomastics in middle Ebro Valley and Southern France during protohistoric period. It aims to explain the issues of this study and how to treat these fragmentary sources. It also proposes some results which need to be developed.
Keywords: epigraphy; anthroponymy; interfaces; method; linguistic contacts